Contemplating Christian ethics and spirituality for sound leadership in organisations - Prof Angelo Nicolaides (Pharos Journal of Theology, 2020)
For the Orthodox believer, and most Christian denominations, Christian ethics applies to Christian faith and positive servant leadership motivations based on deep spirituality which is required to link in a manner which allows for the desired principles, standards, and procedures for actions and a set of divinely inspired virtues to be in place with relevance to all economic activity. In the modern world in which we live there is seemingly very little agreement regarding desired standards of good or ethical behaviour. One’s weltanschauung and culture invariably influence and shape human opinions on business ethics and what constitutes ‘good’ behaviour. There are numerous limitations in modernism when it comes to moral issues and the role religion can play. This article provides a brief explanation of the Christian worldview and the role of spirituality as an alternate approach to probing ethical matters in business. The Orthodox Christian Holy Bible speaks commandingly and expansively on all aspects of life, including desired conduct in business activities. There is indeed a systematic biblical context which apprises the desired practice in business for the global world of commerce.